2017
DOI: 10.1002/ajh.24976
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib‐associated infections: A systematic review and meta‐analysis

Abstract: Ruxolitinib exerts immunosuppressive activity that may increase the risk of infectious complications. We performed a systematic review of the literature with the aim of estimating the risk of infections in patients treated with ruxolitinib. Studies were identified by electronic search of MEDLINE and EMBASE database. Differences in the incidence of infectious events between ruxolitinib and comparison groups were expressed as odds ratios (ORs) and 95% confidence intervals (95% CI). Five phase III randomized clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 57 publications
3
139
2
9
Order By: Relevance
“…There are increasing numbers of reports of infectious complications in patients on ruxolitinib treatment . Ruxolitinib influences the cytokine expression, down‐regulates regulatory T cells and interferes with dendritic cells and natural killer cells . In the presented case consistent with short‐lived therapeutic effect of adoptive T‐cell infusions, ruxolitinib abolished any ELISpot signal even the positive control completely demonstrating the potent ability of this compound to suppress T‐cell responses.…”
Section: Discussionsupporting
confidence: 51%
“…There are increasing numbers of reports of infectious complications in patients on ruxolitinib treatment . Ruxolitinib influences the cytokine expression, down‐regulates regulatory T cells and interferes with dendritic cells and natural killer cells . In the presented case consistent with short‐lived therapeutic effect of adoptive T‐cell infusions, ruxolitinib abolished any ELISpot signal even the positive control completely demonstrating the potent ability of this compound to suppress T‐cell responses.…”
Section: Discussionsupporting
confidence: 51%
“…Nonetheless, long‐term studies have demonstrated a lack of response in some patients and loss of response in the majority of patients . Some patients may not tolerate ruxolitinib because of therapy‐related anemia, thrombocytopenia, or nonhematologic adverse events, in particular, infectious complications . Consequently, ruxolitinib is discontinued by most patients during the first 5 years of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some patients may not tolerate ruxolitinib because of therapy-related anemia, thrombocytopenia, or nonhematologic adverse events, in particular, infectious complications. [10][11][12] Consequently, ruxolitinib is discontinued by most patients during the first 5 years of treatment. In the registration-enabling Controlled Myelofibrosis Study With Oral JAK Inhibitor Treatment (COMFORT)-I and COMFORT-II studies, which enrolled only intermediate-2-risk and high-risk patients, the rate of treatment discontinuation was approximately 50% at 3 years and 75% at 5 years; whereas the expanded-access JAK Inhibitor Ruxolitinib in Myelofibrosis Patients (JUMP) study, which also included intermediate-1-risk patients, reported a discontinuation rate of 35% after 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…At present, however, primary VZV prophylaxis for patients undergoing ruxolitinib treatment is not recommended based on the available data, while secondary prophylaxis may be considered, on a case by case basis, for those experiencing recurrent reactivations or for severe, serious or disseminated VZV infections. The best duration of prophylaxis could not be determined, because the rates of VZV infection did not decrease over time (Lussana et al , ).…”
Section: Clinical Scenario 1 Vzv Reactivationmentioning
confidence: 99%
“…As clinical experience with the use of ruxolitinib increased, both within and outside of a clinical trial setting, the prospect of a drug‐induced, impaired immunosurveillance emerged, suggested by an increased risk of infectious complications and several reports of events that sometimes were atypical in terms of aetiology and clinical presentation (Lussana et al , ; Dioverti et al , ; Polverelli et al , ).…”
mentioning
confidence: 99%